Regulation of Autoimmune Germinal Center Reactions in Lupus-Prone BXD2 Mice by Follicular Helper T Cells - Kim, Young Uk (PLoS One, 2015)
BXD2 mice spontaneously develop autoantibodies and subsequent glomerulonephritis, offering a useful animal model to study autoimmune lupus. Although initial studies showed a critical contribution of IL-17 and Th17 cells in mediating autoimmune B cell responses in BXD2 mice, the role of follicular helper T (Tfh) cells remains incompletely understood. We found that both the frequency of Th17 cells and the levels of IL-17 in circulation in BXD2 mice were comparable to those of wild-type. By contrast, the frequency of PD-1(+)CXCR5(+) Tfh cells was significantly increased in BXD2 mice compared with wild-type mice, while the frequency of PD-1(+)CXCR5(+)Foxp3(+) follicular regulatory T (Tfr) cells was reduced in the former group. The frequency of Tfh cells rather than that of Th17 cells was positively correlated with the frequency of germinal center B cells as well as the levels of autoantibodies to dsDNA. More importantly, CXCR5(+) CD4(+) T cells isolated from BXD2 mice induced the production of IgG from naïve B cells in an IL-21-dependent manner, while CCR6(+) CD4(+) T cells failed to do so. These results together demonstrate that Tfh cells rather than Th17 cells contribute to the autoimmune germinal center reactions in BXD2 mice.